Telemedycyna transgraniczna – problematyka prawa właściwego dla przypadków odpowiedzialności cywilnej podmiotów medycznych na gruncie prawodawstwa unijnego - Nowak, Aleksandra (Wydawnictwo C.H. Beck, 2018)
Health services provided with use of innovative information and telecommunication technology have recently gained popularity in Europe. So-called telemedicine has the potential to become one of the pillars of health care systems – both on the domestic and European level. In this respect, particular attention should be paid to cross-border telemedicine services which – in the absence of European harmonization – are subject of great controversy, notwithstanding their undoubted beneficial effects. This paper provides an overview of the issue, notably in terms of European Union legal framework on telemedicine.
Keywords: cross-border telemedicine; European Union; medical liability; law applicable